1988
DOI: 10.1021/bi00413a034
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 inactivation by 3-alkylsydnones. Mechanistic implications of n-alkyl and n-alkenyl heme adduct formation

Abstract: Incubation of 3-(2-phenylethyl)-4-methylsydnone (PMS) with liver microsomes from phenobarbital-pretreated rats or with reconstituted cytochrome P-450b results in loss of the enzyme chromophore. Chromophore loss is NADPH-dependent even though the sydnone decomposes by an oxygen- but not enzyme-dependent process to give pyruvic acid and, presumably, the (2-phenylethyl)diazonium cation. N-(2-Phenylethyl)protoporphyrin IX and N-(2-phenylethenyl)protoporphyrin IX have been isolated from the livers of rats treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…It is conceivable that this spectrum reflects the presence of SB-N-heme (Fe 3ϩ ) adduct in this in vitro system, because it is similar to that of the purified iron-complexed N-ethylporphyrins, that exhibit absorbance maxima at 442 nm (25). Furthermore, consistent with this possibility, the absolute spectra of phenylacetylene-or 3-alkylsydnone-inactivated P450 2B1 preparations that yield N-modified heme adducts also exhibit a time-dependent increase in a 445 nm shoulder (26,27). It is interesting that no corresponding spectra are detected after inactivation of P450 2B1 by allylisopropylacetamide, or of other P450s by 3,5-dicarbethoxy-2,6-dimethyl-4-ethyl-1,4-dihydropyridene, in spite of the fact that much larger quantities of N-alkylated porphyrins are formed and isolated from such inactivation systems.…”
Section: Sb Epoxidation By P450 2b1 and Its Mutants-supporting
confidence: 53%
“…It is conceivable that this spectrum reflects the presence of SB-N-heme (Fe 3ϩ ) adduct in this in vitro system, because it is similar to that of the purified iron-complexed N-ethylporphyrins, that exhibit absorbance maxima at 442 nm (25). Furthermore, consistent with this possibility, the absolute spectra of phenylacetylene-or 3-alkylsydnone-inactivated P450 2B1 preparations that yield N-modified heme adducts also exhibit a time-dependent increase in a 445 nm shoulder (26,27). It is interesting that no corresponding spectra are detected after inactivation of P450 2B1 by allylisopropylacetamide, or of other P450s by 3,5-dicarbethoxy-2,6-dimethyl-4-ethyl-1,4-dihydropyridene, in spite of the fact that much larger quantities of N-alkylated porphyrins are formed and isolated from such inactivation systems.…”
Section: Sb Epoxidation By P450 2b1 and Its Mutants-supporting
confidence: 53%
“…are potent porphyrinogenic xenobiotics capable of eliciting mechanism-based inactivation of cytochrome P450 (CYP), with concomitant N-alkylprotoporphyrin IX (N-alkylPP) formation and subsequent ferrochelatase (FC) inhibition in rats (Grab et al 1988;Tephly et al 1979). Previously, we have shown that the rat CYP isozymes responsible for N-alkylPP formation, and thus the critical mediators of hepatic porphyrin accumulation, are different for TTMS and 4-ethylDDC (Wong et al 1998).…”
Section: -[(Arythio)ethyl]sydnone (Ttms) and 35-diethoxycarmentioning
confidence: 99%
“…The residue was resuspended in tetrahydrofuran, the radioactivity was measured, and an aliquot was analyzed by reverse-phase HPLC. The heme fraction that contained radioactivity was treated with H2SO4/ CH3OH to derivatize the carboxylic acid groups on the heme moiety to methyl esters, followed by treatment with zinc acetate to form methylated zinc metalloporphyrins (23)(24)(25)(26); it was then analyzed by HPLC. As an alternative approach, the whole hemoglobin was treated in a similar manner; this simultaneously precipitates the protein and derivatizes the heme moiety to the corresponding methyl ester.…”
Section: Chemicalsmentioning
confidence: 99%
“…Concentrated acid and base treatments of the heme fraction did not release any detectable derivative of 1-NP, suggesting that the radioactivity was strongly bound to the heme moiety. Other compounds (for example phenylhydrazine, 3-alkylsydnones, diethylnitrosamine, aminobenzotriazole, and norethindrone) have also been shown to form adducts with the heme moiety of hemoglobin as well as with heme-containing enzymes (23)(24)(25)(26)(43)(44)(45) …”
Section: Analysis Of Hemoglobin Adducts Fliowig the Or Adnistration Omentioning
confidence: 99%